The importance of global economic policy uncertainty in predicting gold futures market volatility: A GARCH‐MIDAS approach. Issue 3 (27th December 2017) - Fang, Libing; Chen, Baizhu; Yu, Honghai; Qian, Yichuo
Abstract : This paper applies the GARCH‐MIDAS model to examine whether information contained in global economic policy uncertainty (GEPU) can help to predict short‐ and long‐term components of the gold futures return variance. Our results show that GEPU positively and significantly forecasts the future monthly volatilities for the aggregate global gold futures market. The forecasting power of GEPU remains strong in an out‐of‐sample setting. Moreover, further out‐of‐sample tests show that the GARCH‐MIDAS model with GEPU and realized volatility outperforms all other specifications, indicating that including low‐frequency GEPU information in the GARCH‐MIDAS model significantly enhances the forecasting ability of the model.